2016
DOI: 10.6024/jmbai.2016.58.1.1862-11
|View full text |Cite
|
Sign up to set email alerts
|

A review of bioactive compounds from marine organisms with special mention on the potential of marine sponges in pharmacological applications

Abstract: A variety of biologically active compounds with unique structures and pharmacological properties have been reported to occur in marine organisms. Demospongiae, an important class of marine sponge is known for producing the largest number and diversity of secondary metabolites isolated till recent times. The review covers the diverse class of bioactive compounds isolated for therapeutic drug applications from different marine organisms. It is an attempt to update the marine research community with results of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The compounds found in the sponge crude extract were like those reported to be found in plant extracts. Kumar and Pal [ 46 ] made a similar observation when they found that D-phytosphingosine, a corresponding 4-hydroxy analog of D-sphinganine, is a significant sphinganoid base found in both higher plants and many invertebrates.…”
Section: Resultsmentioning
confidence: 78%
“…The compounds found in the sponge crude extract were like those reported to be found in plant extracts. Kumar and Pal [ 46 ] made a similar observation when they found that D-phytosphingosine, a corresponding 4-hydroxy analog of D-sphinganine, is a significant sphinganoid base found in both higher plants and many invertebrates.…”
Section: Resultsmentioning
confidence: 78%
“…Extraction of beneficial compounds from these wastes and using them in animal diets as an additive or supplement has been reported in previous studies (Kumar & Pal, 2016;Flick, 1994). It has also been reported that king shrimp's shell has significant amounts of Astaxanthin pigment, flavoring compounds, chitin, etc.…”
Section: Introductionmentioning
confidence: 76%
“…Surely, high value-added compounds and products can be extracted from these wastes if they were properly processed. (Kumar & Pal, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all marine organisms, sponge is the most studied as source of bioactive compounds (Mehbub et al, 2014;Kumar and Pal, 2016). Beesoo et al (2017) reported extract from Neopetrosia exigua contained beta-sitosterol and cholesterol.…”
Section: Introductionmentioning
confidence: 99%